THE UNIQUENESS OF GANCH CARVING ART IN THE DECORATION OF TASHKENT MOSQUES (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This article explores the role of ganch carving art in the decoration of mosques in Tashkent during the late 19th and early 20th centuries.